Public companies in Ecuador and their impact on administrative accounting management - Baque Sánchez, Erick Raúl; Vera Solórzano, Lady Diana; Martínez Robalino, Daniel Andrés; Maldonado Alvarado, Edison Cristóbal (mktDESCUBRE; Vol 1 No Edición Es (2024): 7th International Scientific Congress of Administrative and Financial Sciences FADE 2023, 2024)
This present study in the undertakings publish Ecuadoran to analyze the incidence of administrative accounting management, which includes internal control as the key instrument to maintain the reliability of financial information, against fraud, efficiency and operational effectiveness and the environment in the one that organizations are inserted, evidenced in recent years, where constant searches for better organizational practices are required and the increase in complexity in internal processes, as well as the competencies of the ideal human resources to conduct them. In this research, a situational analysis of administrative accounting management and its incidence in public companies in Ecuador is carried out, using information obtained from different reliable secondary and primary sources. Through the situational analysis carried out, current problems were identified, as well as the issues on which to decide, potential problems and other important objectives and projects to solve them. A resolution plan was proposed that includes; action, goals and responsibilities to be fulfilled immediately, in the short and medium term. Problems were identified in the selected companies, whose limits were not clearly defined. The situational analysis covered at the same time decision-making and the resolution of useful problems for the administrative management of Ecuadorian public companies, which have a negative impact on PIB growth, after the confinement produced by the current pandemic that is hitting the world.